Zinc blende and wurtzite CoO polymorph nanoparticles: Rational synthesis and commensurate and incommensurate magnetic order. (September 2019) - Golosovsky, I.V.; Estrader, M.; López-Ortega, A.; Roca, A.G.; López-Conesa, L.; Del Corro, E.; Estradé, S.; Peiró, F.; Puente-Orench, I.; Nogués, J.
Abstract : Highlights: The conditions to synthesize wurtzite and zinc blende CoO polymorphs using thermal decomposition of cobalt (II) acetylacetonate are described. The structural characterization of the wurtzite nanoparticles has established the presence of planar defects. In depth analysis of the neutron diffraction patterns with a careful description of the magnetic structure of both the CoO zinc blende and wurtzite nanoparticles and how they were determined. The zinc blende CoO nanoparticles are antiferromagnetic, with a 3rd type magnetic ordering in a face-centered cubic lattice and a Néel temperature of T N ∼ 203 K. The wurtzite CoO nanoparticles have a complex magnetic order with two different components and a Néel temperature of T N ∼ 109 K. One of the components is antiferromagnetic (2nd type in a wurtzite structure), while the other one is incommensurate with the magnetic moments confined in the ab -plane. Abstract: On the nanoscale, CoO can have different polymorph crystal structures, zinc blende and wurtzite, apart from rock salt, which is the stable one in bulk. However, the magnetic structures of the zinc blende and wurtzite phases remain virtually unexplored. Here we discuss some of the main parameters controlling the growth of the CoO wurtzite and zinc blende polymorphs by thermal decomposition of cobalt (II) acetylacetonate. In addition, we present a detailed neutron diffraction study of oxygen deficient CoO (CoO0.70–0.75 ) nanoparticles with zinc blende (∼15 nm) and wurtzite (∼30 nm) crystal structures to unravel their magnetic order and its temperature evolution. The magnetic order of the zinc blende nanoparticles is antiferromagnetic and appears at the Néel temperature T N ∼ 203 K. It corresponds to the 3rd type of magnetic ordering in a face-centered cubic lattice with magnetic moments aligned along a cube edge. The magnetic structure in the wurtzite nanoparticles turned out to be rather complex with two perpendicular components. One component is incommensurate, of the longitudinal spin wave type, with the magnetic moments confined in the ab -plane. In the perpendicular direction, this magnetic order is uncorrelated, forming quasi-two-dimensional magnetic layers. The component of the magnetic moment, aligned along the hexagonal axis, is commensurate and corresponds to the antiferromagnetic order known as the 2nd type in a wurtzite structure. The Néel temperature of wurtzite phase is estimated to be ∼109 K. The temperature dependence of the magnetic reflections confirms the reduced dimensionality of the incommensurate magnetic order. Incommensurate magnetic structures in nanoparticles are an unusual phenomenon and in the case of wurtzite CoO it is probably caused by structural defects (e.g., vacancies, strains and stacking faults).